Address on the Life and Services of Gen. Lewis A. Armistead - James E. Poindexter (1909)
Address on the Life and Services of Gen. Lewis A. Armistead, delivered by Rev. James E. Poindexter, Late Captain in Thirty-Eighth Virginia Regiment, Armistead's Brigade, Pickett's Division, Before R. E. Lee Camp, No. 1, Confederate Veterans, Richmond, VA., January 29, 1909.